The Legislative Framework of Public Utility Concessions Award : A Comparative Study - M.ali, Mardin; Hamad, Mariwan (Journal of Legal Sciences, 2022)
Public constructions contracts and concession, have been a link between the public and private sector for decades and we may find serious  international efforts to consider it as an effective economic and legal means of providing public services(legislative framework), in the same time prevents states from drowning in loans, regrettably that Iraqi and Arab jurisprudence is still influenced by  old version of oil concession agreements,  in its research writings about the partnership between public sector and private sector. We have studied in detail the legal mechanism of concession award especially in France, We also studied the position of Egyptian legislation and focused on constitutional law, which outlines the established machinery and thus the position of Iraq's weak legislator.